PROBLEMS AND LIMITATIONS IN PREVENTING AND SUPPRESSING CORRUPTION IN COMMUNITY ENTERPRISE GROUPS UNDER THE COMMUNITY ENTERPRISE PROMOTION ACT 2005 - Saensuk, Suraswadee; Wiriyajaroenkit, Chatchay; Suranna , Suthatip; Savetphataraphaisan, Preechawach (Journal of Liberal Arts and Management Science Kasetsart University, 2025)
This study has three primary objectives under the framework of the Community Enterprise Promotion Act, B.E. 2548 (2005): 1) to examine the legal framework and transparency audit processes governing Community Enterprises (CEs); 2) to analyze the problems and limitations in preventing and suppressing corruption within these enterprises; and 3) to propose viable solutions to address these challenges. Employing a qualitative research methodology, the study involves an in-depth analysis of legal statutes, pertinent regulations, and actual case studies. The principal finding indicates that the Act has inadvertently created a "governance vacuum". Specifically, the absence of mandatory provisions for internal control, financial auditing, and transparency, coupled with the operational autonomy granted by the law, has culminated in several tangible problems. This situation exposes CEs to significant corruption risks, including non-transparent financial management, conflicts of interest, and the absence of effective grievance mechanisms. Consequently, this paper proposes key systemic solutions: 1) amending subsidiary legislation related to CE registration renewal to mandate the submission of basic financial reports and conflict of interest disclosures; and 2) applying existing governance frameworks by adapting the "Guidelines on Appropriate Internal Control Measures for Juristic Persons" from the Office of the National Anti-Corruption Commission (NACC). This adaptation aims to fit the specific context of CEs, thereby establishing a clear and actionable governance mechanism.